2002
DOI: 10.1021/ja0170044
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally Stable Ordered Mesoporous Titanosilicates with Highly Active Catalytic Sites

Abstract: Mesoporous titanosilicates (MTS-9) are successfully prepared in strong acidic media by a two-step synthesis. MTS-9 has an ordered hexagonal structure and exhibits superior hydrothermal stability and high catalytic activity for the oxidation of the small molecules of phenol and styrene and also of the bulky molecule of trimethylphenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
131
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(137 citation statements)
references
References 34 publications
6
131
0
Order By: Relevance
“…In order to minimize diffusional limitations in the microporous network of MFI zeolites, several approaches have been developed in the last few years to induce intra-crystalline mesoporosity including hard templating [4][5][6], soft templating [7,8], demetalation [9][10][11][12][13][14][15] and modified crystallization methods [16,17]. Unfortunately, several of these approaches provide structures which are not hydrothermally stable in a manner similar to nanocrystalline zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize diffusional limitations in the microporous network of MFI zeolites, several approaches have been developed in the last few years to induce intra-crystalline mesoporosity including hard templating [4][5][6], soft templating [7,8], demetalation [9][10][11][12][13][14][15] and modified crystallization methods [16,17]. Unfortunately, several of these approaches provide structures which are not hydrothermally stable in a manner similar to nanocrystalline zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…However, M41S materials generally exhibit weak acidity and low hydrothermal stability due to their amorphous frameworks. As a consequence, new synthesis strategies have been developed to obtain materials which com-bine the advantages of mesoporous materials and those of zeolites [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. For example, Corma et al [21] reported a post-synthesis dealumination process via steaming or acid leaching on full-grown zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last couple of years, several simple and reliable approaches have been developed to form micro/mesoporous combined materials using zeolite nanoparticles or zeolite seeds as the silica source [31][32][33][34][35][36]. However, most of the published reports on composite catalysts have focused on one-dimensional materials (such as MCM-41 or SBA-15) as the mesostructured component, although three-dimensional materials, such as cubic MCM-48, are more interesting from the viewpoint of catalysis due to the interwoven pore system, which allows the sufficient diffusion of reactants within the pores, subsequently leading to a better catalytic performance [37].…”
Section: Introductionmentioning
confidence: 99%
“…from the zeolitic nanoclusters which are present in the seed precursors of ZSM-5, TS-1(MFI with ~ 0.5 nm pore size) and zeolite beta (BEA with ~0.6 nm pore size), all synthesized under basic conditions. [12][13][14][15][16] Under neutral conditions and with non-ionic surfactants, aluminosilicate mesostructures with wormhole pore features were also synthesized using precursor mixtures of zeolites Y, ZSM-5 and Beta. 17 These materials exhibited hydrothermal stability, but showed low surface areas and small pore volumes.…”
Section: Iv-1 Backgroundmentioning
confidence: 99%